Effects of acerola fruit extract on sensory and shelf-life of salted beef patties from grinds differing in fatty acid composition. (January 2015) - Realini, C.E.; Guàrdia, M.D.; Díaz, I.; García-Regueiro, J.A.; Arnau, J.
Abstract: The effects of added acerola fruit extract on sensory and shelf-life of beef patties were evaluated. Ground beef was obtained from young bulls fed one of four diets (CON: control, LIN: linseed, CLA: conjugated linoleic acid, LINCLA: LIN plus CLA). Pre-salted (1.8% w/w) beef patties (7.7% fat) with (0.15% w/w) or without acerola were packed in modified atmosphere (80%O2 :20%CO2 ) and displayed in a retail case for 8 days. There were no interactions between diet and antioxidant treatments. LIN and/or CLA had no effect on color and lipid stability during display. However, LIN increased n − 3 fatty acids in beef and tended to increase intensity of rancid flavor. Addition of acerola extended shelf-life by at least 3 days by improving color and lipid stability and a decreased trend in intensity of rancid flavor of patties without affecting microbial counts. Thus, the use of acerola as a natural antioxidant can be considered an effective method to retard color and lipid oxidation in beef patties. Highlights: Linseed and conjugated linoleic acid had no effect on beef color or lipid stability. Linseed increased omega-3 fatty acids and tended to increase rancid flavor of patties. Acerola fruit extract (0.15% w/w) extended shelf-life of patties by at least 3 days. Acerola retarded color and lipid oxidation of beef patties displayed in MAP. Acerola tended to reduce rancid flavor and had no effect on microbial counts.